The Influence Of Social Media, Customer Testimonials, Content Quality, And User Interaction On Purchase Intention Of Skincare Products In Bengkulu - Utomo, M. Fredi; Soleh , Ahmad; Abi, Yudi Irawan (Universitas Dehasen Bengkulu, 2025)
In line with the advancements of the era, beauty is not only a necessity for the general public but also a prospective business opportunity, as evident in the growing skincare product industry year after year. The aim of this study is to determine whether social media, content quality, customer testimonials, and user interaction influence the purchase intention of skincare products in Bengkulu. This research employs a quantitative approach. Data collection was conducted using a questionnaire technique, with a sample size of 115 respondents. The results of the study indicate that the multiple linear regression model is Y = 0,005 + 0,276 X1 + 0,081 X2 + 0,360 X3 + 0,283X4 + 0,200. The positive coefficients suggest a positive or direct relationship between the variables of social media (X1), customer testimonials (X2), content quality (X3), user interaction (X4), and purchase intention (Y) for skincare products in Bengkulu. The social media test (X1) shows that tcalculated=6.576>ttable=1.981tcalculated = 6.576 > ttable = 1.981 and significance p=0.000<0.05p = 0.000 < 0.05, meaning the hypothesis Ha is accepted and Ho is rejected, indicating that social media has a positive and significant impact on the purchase intention of skincare products in Bengkulu. The customer testimonials test (X2) shows tcalculated=2.247>ttable=1.981tcalculated = 2.247 > ttable = 1.981 and significance p=0.027<0.05p = 0.027 < 0.05, meaning the hypothesis Ha is accepted and Ho is rejected, indicating that customer testimonials have a positive and significant effect on the purchase intention of skincare products in Bengkulu. The content quality test (X3) shows tcalculated =7.803>ttable=1.981tcalculated = 7.803 > ttable = 1.981 and significance p=0.000<0.05p = 0.000 < 0.05, meaning the hypothesis Ha is accepted and Ho is rejected, indicating that content quality has a positive and significant impact on the purchase intention of skincare products in Bengkulu. The user interaction test (X4) shows tcalculated=5.427>ttable=1.981tcalculated = 5.427 > ttable = 1.981 and significance p=0.000<0.05 p= 0.000 < 0.05, meaning the hypothesis Ha is accepted and Ho is rejected, indicating that user interaction has a positive and significant effect on the purchase intention of skincare products in Bengkulu. Based on the comparison of the F-calculated value (12.025) with the F-table value (2.30), since Fcalculated>FtableFcalculated > Ftable, it can be concluded that the hypothesis is accepted, meaning there is a simultaneous influence of social media (X1), customer testimonials (X2), content quality (X3), and user interaction (X4) on the purchase intention (Y) for skincare products in Bengkulu. This is supported by the significance level of p=0.000<0.05p = 0.000 < 0.05